Development and Characterization of a New Scaffold Bio-composite of Chitosan Coated Bioglass (R) for Bone Tissue Engineering - Posada, J.; Li, W.; Escobar, D.; Ossa, C.; Pavon, J. J.; Boccaccini, Aldo R. (2013)
Several research groups and projects are aiming to find materials for scaffolding that allow the growing of bone tissue in vitro at laboratory and a guided regeneration of tissues in vivo after implantation [1-2]. The Bioglass (R) (BG) has shown interesting features for bone tissue engineering, but their mechanical properties are not adequate for direct implantation of dense or porous scaffolds. In this work, we produced porous scaffolds with microparticulate BG, by the slurry dipping method, and then proceeded to coat the samples with chitosan (CHI), to biofunctionalize the surface and improve the mechanical properties. The coatings integrated correctly to the scaffolds (proved by FT-IR) and the mechanical properties were similar to human cancellous bone.
Keywords: Bioactive glass; chitosan; scaffolds; bone tissue engineering; slurry dipping